Soil nutrients and crop yield response to conservation-effective management practices in the sub-humid highlands agro-ecologies of Kenya - M.N. Kiboi; F.K. Ngetich; M.W. Mucheru-Muna; J. Diels; D.N. Mugendi (Heliyon, 2021)
Crop productivity in most smallholder farming systems in Sub-Saharan Africa experience low use of soil amendment resources, low and erratic rainfall, frequent dry spells, and droughts. Rain-fed agriculture has a high crop yield potential if rainfall and soil nutrient input resources are utilized effectively. Thus, in 2011, we set up an on-farm experiment in Meru South (sub-humid) and Mbeere South (marginal sub-humid) sub-counties in upper Eastern Kenya to assess conservation-effective management (CEM) practices effects on maize (Zea Mays L.) yields response and soil nutrients. The CEM practices were; tied ridging (TR), mulching (MC), and minimum tillage (MT), with conventional tillage (CT) as a control. There were frequent dry spells and droughts during the experimental period. The experiment ran for four seasons, from the long rains season of 2011 (LR11), short rains seasons of 2011 (SR11), long rains season of 2012 (LR12), short rains 2012 (SR12), and long rains season of 2013 (LR13). In Meru South, TR and MT treatments had significantly higher phosphorus content (100% and 66%, respectively) than the control. Also, in the same site, Cu and Zn were high in MT than in CT treatments. In the Mbeere South site, the aboveground biomass yield was significantly higher in TR treatment (by 71%) than CT during SR11, while in LR12 season, it significantly increased by 72% and 46% under MC and TR treatments, respectively, than the control. The TR treatment had significantly higher aboveground biomass than the control (84% and 115%) in the SR12 and LR13 seasons. In Meru South, MC treatment had significantly higher aboveground biomass, which was significantly higher, by 39%, during the SR11 season and 46% in TR treatment in SR12 season than the control. This study highlighted tied ridging as the best-fit practice for enhancing maize crop aboveground biomass production in rain-fed farming systems of marginal lands and sub-humid regions receiving unreliable rainfall. Further, we recommend longer-term experimentation to explore CEM effects on soil nutrients.